Nepomorpha, Gerromorpha and Leptopodomorpha (Hemiptera: Heteroptera) of the Tuscan Archipelago (Italy) - Cianferoni, Fabio; Rocchi, Saverio; Terzani, Fabio (Zootaxa, 2013)
This paper provides the first checklists for Nepomorpha (12 spp.), Gerromorpha (10 spp.) and Leptopodomopha (5 spp.) of the Tuscan Archipelago; summarizing and updating the knowledge for this area. The presence of the family Micronec-tidae is recorded for the first time in the Archipelago, as well as six species: Nepomorpha — Micronecta scholtzi (Fieber, 1860), Sigara selecta (Fieber, 1848), S. stagnalis (Leach, 1817), S. lateralis (Leach, 1817); Gerromorpha — Gerris asper (Fieber, 1860); Leptopodomorpha — Saldula palustris (Douglas, 1874); increasing the numbers of aquatic Heteroptera sensu lato from 21 to 27 species. The three infraorders are present in only four of the seven major islands of the Tuscan Archipelago (Capraia, Elba, Montecristo and Giglio). The Isle of Elba has been scarcely investigated until now: ten spe-cies are newly recorded for this island (doubling the number to 20 spp.), whilst another species has been first recorded for Giglio Island. The most remarkable finding is Gerris asper (Fieber, 1860) on Elba, a species inhabiting marshy areas that is very rare to Italy. Notonecta glauca Linnaeus, 1758 is excluded from the fauna of the Tuscan Archipelago.